TRIM22 governs tumorigenesis and protects against endometrial cancer-associated cachexia by inhibiting inflammatory response and adipose thermogenic activity - Liping Zhang; Quanrong Li; Meiting Wu; Xiushan Feng; Weichao Dai; Peifang Chen; Dezhao Chen; Zhiqun Zheng; Xiaoyan Lin; Gang Wei (Cancer & Metabolism)
Abstract Background Endometrial cancer (EC) is one of the most common cancers in women, with a short overall survival and poor prognosis. Besides the biologically aggressive EC properties, Cancer-associated cachexia is the main factor. However, the detailed mechanism underlying EC-related cachexia and its harmful effects on EC progression and patient prognosis remains unclear. Methods For clinical specimen and the vitro experiment, we detected TRIM22 expression level, EC patients’ survival time, EC cell functional change, and adipose thermogenic changes to identify the function of TRIM22 in EC progression, EC-associated cachexia, and their molecular mechanisms. Then, for the vivo experiment, we exploited the xenografts in mice to identify the function of TRIM22 again, and to screen the drug therapeutic schedule. Results Herein, we demonstrated that TRIM22 inhibited EC cell growth, invasion, and migration. Interleukin (IL)-6 mediated brown adipose tissue activation and white adipose tissue browning which induced EC-related cachexia. TRIM22 suppressed the EC cells’ secretion of IL-6, and IL-6 mediated EC-related cachexia. Mechanistically, TRIM22 inhibited EC progression by suppressing the nucleotide-binding oligomerization domain 2(NOD2)/nuclear factor-kappaB (NF-κB) signaling pathway, with the purpose of impeding the production of IL-6. Moreover, we revealed that TRIM22 inhibited EC-associated cachexia by suppressing the IL-6/IL-6 receptor (IL-6R) signaling pathway. Therapeutically, we demonstrated that combination treatment with a TRIM22 inducer (progesterone) and a thermogenic inhibitor (IL-6R antibody) synergistically augmented the antitumor efficacy of carbotaxol (carboplatin and paclitaxel), in vivo. Conclusion Our data reveals that TRIM22-EC-IL-6-cachexia cross-communication has important clinical relevance and that the use of combined therapy holds great promise for enhancing the efficacy of anti-ECs. (Fig. graphical abstract) Graphical abstract